PLCs HMIs and troubleshooting - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
The PLCs: HMIs and Troubleshooting training program, or unit, is designed to familiarize trainees with human-machine interfaces and how they can be used in the troubleshooting of programmable logic controller system problems. After completing this program, the trainees should be able to identify various types of HMIs and explain how they are connected and used. They should also be able to describe the five steps of troubleshooting and explain how to use those steps and an HMI to troubleshoot a problem in a PLC system.
Keywords: Human-machine systems